Computer and Computing Technologies in Agriculture III Third IFIP TC 12 International Conference, CCTA 2009, Beijing, China, October 14-17, 2009, Revised Selected Papers - Li, Daoliang; Zhao, Chunjiang (IFIP Advances in Information and Communication Technology, 2010)
I want to express my sincere thanks to all authors who submitted research papers to support the Third IFIP International Conference on Computer and Computing Te- nologies in Agriculture and the Third Symposium on Development of Rural Infor- tion (CCTA 2009) held in China, during October 14-17, 2009. This conference was hosted by the CICTA (EU-China Centre for Information & Communication Technologies, China Agricultural University), China National En- neering Research Center for Information Technology in Agriculture, Asian Conf- ence on Precision Agriculture, International Federation for Information Processing, Chinese Society of Agricultural Engineering, Beijing Society for Information Te- nology in Agriculture, and the Chinese Society for Agricultural Machinery. The pla- num sponsor includes the Ministry of Science and Technology of China, Ministry of Agriculture of China, Ministry of Education of China, among others. The CICTA (EU-China Centre for Information & Communication Technologies, China Agricultural University) focuses on research and development of advanced and practical technologies applied in agriculture and on promoting international communi- tion and cooperation. It has successfully held three International Conferences on C- puter and Computing Technologies in Agriculture, namely CCTA 2007, CCTA 2008 and CCTA 2009. Sustainable agriculture is the focus of the whole world currently, and therefore the application of information technology in agriculture is becoming more and more - portant. 'Informatized agriculture' has been sought by many countries recently in order to scientifically manage agriculture to achieve low costs and high incomes.